Distinct structural and dynamic components of portal hypertension in different animal models and human liver disease etiologies. Issue 3 (20th December 2021) - Königshofer, Philipp; Hofer, Benedikt Silvester; Brusilovskaya, Ksenia; Simbrunner, Benedikt; Petrenko, Oleksandr; Wöran, Katharina; Herac, Merima; Stift, Judith; Lampichler, Katharina; Timelthaler, Gerald; Bauer, David; Hartl, Lukas; et al.
Abstract: Background and Aims: Liver fibrosis is the static and main (70%‐80%) component of portal hypertension (PH). We investigated dynamic components of PH by a three‐dimensional analysis based on correlation of hepatic collagen proportionate area (CPA) with portal pressure (PP) in animals or HVPG in patients. Approach and Results: Different animal models (bile duct ligation: n = 31, carbon tetrachloride: n = 12, thioacetamide: n = 12, choline‐deficient high‐fat diet: n = 12) and patients with a confirmed single etiology of cholestatic (primary biliary cholangitis/primary sclerosing cholangitis: n = 16), alcohol‐associated ( n = 22), and metabolic (NASH: n = 19) liver disease underwent CPA quantification on liver specimens/biopsies. Based on CPA‐to‐PP/HVPG correlation, potential dynamic components were identified in subgroups of animals/patients with lower‐than‐expected and higher‐than‐expected PP/HVPG. Dynamic PH components were validated in a patient cohort ( n = 245) using liver stiffness measurement (LSM) instead of CPA. CPA significantly correlated with PP in animal models (Rho = 0.531; p < 0.001) and HVPG in patients (Rho = 0.439; p < 0.001). Correlation of CPA with PP/HVPG varied across different animal models and etiologies in patients. In models, severity of hyperdynamic circulation and specific fibrosis pattern (portal fibrosis: p = 0.02; septa width: p = 0.03) were associated with PH severity. In patients, hyperdynamic circulation ( p = 0.04), vascular dysfunction/angiogenesis (VWF‐Ag: p = 0.03; soluble vascular endothelial growth factor receptor 1: p = 0.03), and bile acids ( p = 0.04) were dynamic modulators of PH. The LSM‐HVPG validation cohort confirmed these and also indicated IL‐6 ( p = 0.008) and hyaluronic acid (HA: p < 0.001) as dynamic PH components. Conclusions: The relative contribution of "static" fibrosis on PH severity varies by type of liver injury. Next to hyperdynamic circulation, increased bile acids, VWF‐Ag, IL‐6, and HA seem to indicate a pronounced dynamic component of PH in patients.